Phosphatidylcholine and Sphingomyelin Profiles Vary in Bos taurus indicus and Bos taurus taurus In Vitro- and In Vivo-Produced Blastocysts - Sudano, Mateus J. [UNESP]; Santos, Vanessa G.; Tata, Alessandra; Ferreira, Christina R.; Paschoal, Daniela M. [UNESP]; Machado, Rui; Buratini, Jose [UNESP]; Eberlin, Marcos N.; Landim-Alvarenga, Fernanda da Cruz [UNESP] (Soc Study Reproduction, 2012)
Lipid droplets, subspecies (Bos taurus indicus vs. Bos taurus taurus), and in vitro culture are known to influence cryopreservation of bovine embryos. Limited information is available regarding differences in membrane lipids in embryo, such as phosphatidylcholines (PC) and sphingomyelins (SM). The objective of the present study was to compare the profiles of several PC and SM species and relate this information to cytoplasmic lipid levels present in Nellore (B. taurus indicus) and Simmental (B. taurus taurus) blastocysts produced in vitro (IVP) or in vivo (ET). Simmental and IVP embryos had more cytoplasmic lipid content than Nellore and ET embryos (n = 30). Blastocysts were submitted to matrix-assisted laser desorption/ionization mass spectrometry. Differences in the PC profile were addressed by principal component analysis. The lipid species with PC (32: 1) and PC (34: 1) had higher ion abundances in Nellore embryos, whereas PC (34: 2) was higher in Simmental embryos. IVP embryos had less abundant ions of PC (32: 1), PC (34: 2), and PC (36: 5) compared to ET embryos. Moreover, ion abundance of PC (32: 0) was higher in both Nellore and Simmental IVP embryos compared to ET embryos. Therefore, mass spectrometry profiles of PC and SM species significantly differ with regard to unsaturation level and carbon chain composition in bovine blastocysts due to subspecies and in vitro culture conditions. Because PC abundances of Nellore and Simmental embryos were distinct (34: 1 vs. 34: 2), as were those of IVP and ET embryos (32: 0 vs. 36: 5), they are potential markers of postcryopreservation embryonic survival.
Keywords: cryopreservation; cryotolerance biomarkers; embryo; in vitro culture; lipidomics; MALDI-MS; mass spectrometry; taurine; zebuine